Use of Platelet-Rich Plasma and Platelet-Rich Fibrin in Dentistry and Oral Surgery: Introduction and Review of the Literature. (June 2019) - Feigin, Kristina; Shope, Bonnie
Platelet concentrates, mostly represented by platelet-rich plasma and platelet-rich fibrin, have gained significant interest in various medical and oral disciplines because of their potential to stimulate and boost regeneration of hard and soft tissues. Prepared from the patient's own blood, they have been tested and used in various different surgical fields including oral and maxillofacial surgery. The effects of these biomaterials are described to be a result of the large concentration of platelets which contain a wide range of growth factors. The aim of this article is to introduce the principle and function of these platelet concentrates, to review their preparation, and to provide a comprehensive examination of the published oral and maxillofacial literature on this subject.